Drug monitoring of sunitinib in patients with advanced solid tumors: a monocentric observational French study. (10th November 2017) - Cabel, Luc; Blanchet, Benoit; Thomas‐Schoemann, Audrey; Huillard, Olivier; Bellesoeur, Audrey; Cessot, Anatole; Giroux, Julie; Boudou‐Rouquette, Pascaline; Coriat, Romain; Vidal, Michel; Saidu, Nathaniel E. B.; Golmard, Lisa; et al.
Abstract: Therapeutic drug monitoring (TDM) could be helpful in oral targeted therapies. Data are sparse to evaluate its impact on treatment management. This study aimed to determine a threshold value of plasma drug exposure associated with the occurrence of grade 3–4 toxicity, then the potential impact of TDM on clinical decision. Consecutive outpatients treated with sunitinib were prospectively monitored between days 21 and 28 of the first cycle, then monthly until disease progression. At each consultation, the composite AUCƬ, ss (sunitinib + active metabolite SU12662) was assayed. The decisions taken during each consultation were matched with AUCƬ, ss and compared to the decisional algorithm based on TDM. A total of 105 cancer patients and 288 consultations were matched with the closest AUCƬ, ss measurement. The majority (60%) of the patients had metastatic renal clear‐cell carcinoma (mRCC). Fifty‐five (52%) patients experienced grade 3–4 toxicity. Multivariate analysis identified composite AUCƬ, ss as a parameter independently associated with grade 3–4 toxicity ( P  < 0.0001). Using the ROC curve, the threshold value of composite AUCƬ, ss predicting grade ≥3 toxicity was 2150 ng/mL/h (CI 95%, 0.6–0.79%; P  < 0.0001). At disease progression in patients with mRCC, AUCƬ, ss tended to be lower than the one assayed during the first cycle (1678 vs. 2004 ng/mL/h, respectively, P  = 0.072). TDM could have changed the medical decision for sunitinib dosing in 30% of patients at the first cycle of treatment, and in 46% of the patients over the whole treatment course. TDM is routinely feasible and may both contribute to improve toxicity management and to identify sunitinib underexposure at the time of disease progression.